Contact investigation of tuberculosis in Shanghai, China: A 13-year cohort. (March 2023) - Zhou, Meiling; Wang, Luqi; Li, Meng; Zou, Jinyan; Li, Yong; Li, Jin; Lu, Liping; Guo, Xiaoqin; Wang, Weibing
Abstract: Objectives: Tuberculosis (TB) contact investigation is an effective strategy for TB control. We established a close-contact cohort to evaluate the effect of contact investigation in Shanghai, China. Methods: Close contacts of bacteria-positive TB cases diagnosed from 2009 to 2018 in the Songjiang District of Shanghai were screened and followed up until 2021 through symptom examination or other alternatives, and the incidence and risk factors for developing active TB among close contacts were assessed by survival analysis and WGS. Results: 7018 close contacts of 2861 bacteria-positive TB cases were investigated. The median follow-up time was 7.4 years. 97 close contacts (185/100, 000, 95%CI: 151-226) developed TB. Survival analysis showed that index cases who were in younger age groups, living in urban settings, smear-positive, and reported a healthcare-seeking delay for TB had higher risks of generating contact cases. Close contacts with matched strains developed TB at an average of 26.5 months based on WGS. Conclusion: A 2-year ideally longer follow-up for close contacts would be beneficial. To improve early case detection, more attention needs to be paid to those contacts whose index cases were living in urban settings, were smear-positive, had a healthcare-seeking delay for TB, and/or were aged ≤18 years.